2016
DOI: 10.3171/2014.9.jns131422
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI, resting state fMRI, and DTI for predicting verbal fluency outcome following resective surgery for temporal lobe epilepsy

Abstract: 929cliNical article J Neurosurg 124:929-937, 2016 P redicting outcome following resective brain surgery remains a high-priority goal in neurology and neurosurgery. Recently, a need for classifying surgical outcome on the basis of functional status, such as cognition, rather than just seizure control, has been articulated. 44 A number of neuroimaging techniques give us insight into the neuroanatomical correlates of cognition. These techniques are increasingly being used as part of presurgical planning algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…For example, rsfMRI connectivity has been evaluated to guide or predict outcomes in neurosurgical approaches in brain injury [97], brain tumors [98], and epilepsy [99], and deep brain stimulation [100]. In addition, the effects of noninvasive brain stimulation have been linked to the connectivity profiles of intrinsic networks across many diseases.…”
Section: Optimism For Clinical Identification Prediction and Translmentioning
confidence: 99%
“…For example, rsfMRI connectivity has been evaluated to guide or predict outcomes in neurosurgical approaches in brain injury [97], brain tumors [98], and epilepsy [99], and deep brain stimulation [100]. In addition, the effects of noninvasive brain stimulation have been linked to the connectivity profiles of intrinsic networks across many diseases.…”
Section: Optimism For Clinical Identification Prediction and Translmentioning
confidence: 99%
“…Among the imaging measures, DTI had the highest beta value, explaining 32% of the variance in fluency decline. Importantly, this study found that the pre to postoperative change in these imaging variables was more predictive than baseline imaging values or baseline clinical variables (i.e., duration of epilepsy, age, baseline fluency score, and baseline Verbal IQ) (Osipowicz, Sperling, Sharan, & Tracy, 2015). These data suggest that although preoperative imaging and clinical factors are important predictors of language outcome, the degree of postoperative reorganization that ensues within language networks may be the most important determinant of outcome.…”
Section: Dti and Language Network In Tlementioning
confidence: 89%
“…To our knowledge, only one study has addressed this question. In a cohort of 15 patients, Osipowicz et al (2015) concluded that rather than any one measure, a combination of DTI, fMRI, and rsfMRI metrics provided the best predictive model, explaining 52% of the variance in post-operative semantic fluency decline and correctly classifying 87% of patients as having good versus poor fluency outcome. Among the imaging measures, DTI had the highest beta value, explaining 32% of the variance in fluency decline.…”
Section: Dti and Language Network In Tlementioning
confidence: 99%
“…Furthermore, new functional neuroimaging procedures that explore more widespread network disruptions commonly found in MTLE, such as diffusion-tensor imaging (DTI), combined with fMRI activation studies, may significantly improve the prediction of postsurgical memory (Osipowicz et al, 2016).…”
Section: Potential Modern Surrogate Markers Of Epileptogenesis and Epmentioning
confidence: 99%